An assessment of emergency care capacity at hospitals in Harare Metropolitan: A descriptive cross-sectional study - Deka, Prince (Division of General Surgery, 2025)
Objectives of literature review. The literature review aims to: To describe Zimbabwe's country profile, highlighting key demographic, economic, and social factors impacting its healthcare system. To describe the evolution of emergency medicine in Africa, emphasising the contextual factors derailing its development in Zimbabwe. To give an overview of African EC systems, focusing on Zimbabwe's unique challenges and advancements. To discuss the significance of and tools for appraising EC systems.